Phosphate polyanion materials as high-voltage lithium-ion battery cathode: A review - JinKiong, Ling; Chelladurai, Karuppiah; Syam G., Krishnan; M. V., Reddy; Izan Izwan, Misnon; Mohd Hasbi, Ab. Rahim; Chun-Chen, Yang; Rajan, Jose (American Chemical Society, 2021)
Followed by decades of successful efforts in developing cathode materials for high specific capacity lithiumion batteries, currently the attention is on developing a high voltage battery (>5 V vs Li/Li+ ) with an aim to increase the energy density for their many fold advantages over conventional <4 V batteries. Among the various cathode materials, phosphate polyanion materials (LiMPO4, where M is a single metal or a combination of metals) showed promising candidacy given their high electrochemical potential (4.8−5 V vs Li/Li+), long cycle stability, low cost, and achieved specific capacity (∼165 mAh·g−1) near to its theoretical limit (170 mAh·g−1). In this review, factors affecting the electrochemical potential of the cathode materials are reviewed and discussed. Techniques to improve the electrical and ionic conductivities of phosphate polyanion cathodes, namely, surface coating, particle size reduction, doping, and morphology engineering, are also discussed. A processing−property correlation in phosphate polyanion materials is also undertaken to understand relative merits and drawbacks of diverse processing techniques to deliver a material with targeted functionality. Strategies required for high-voltage phosphate polyanion cathode materials are envisioned, which are expected to deliver lithium-ion battery cathodes with higher working potential and gravimetric specific capacity